Understanding and evaluating visual guidance quality inside passenger terminals - a cognitive and quantified approach. Issue 4 (4th July 2019) - Xu, Ran; Su, Xing; Xia, Haishan
ABSTRACT: Using the findings from visual cognitive psychology and computer vision, this study proposes a method that can predict how passenger visual attention to indoor visual guidance elements will affect the visual guidance quality inside passenger terminals. A saliency model is used to simulate the human visual attention, so as to understand how the visual guidance elements and visual noise are cognitively perceived by passengers. For every possible origin and destination node combination, the length and probability of the path that passengers are most likely to take (LP) are compared with the respective shortest path (SP). The overall evaluation of the terminal's visual guidance quality can be expressed by the Extra Walking Index. The validity of the developed evaluation method is verified and it is then applied in a case study. The method can be used as a supporting tool for architects to identify relevant architectural features in the design phase and optimize them accordingly; in addition, it can also provide existing passenger terminals with specific improvement suggestions.